IMPLEMENTASI KEBIJAKAN UPAH MINIMUM KOTA (UMK) DI KOTA CILEGON - Salma Nurcholisa; Dyah Lituhayu (Journal of Management and Public Policy, 2026)
The Municipal Minimum Wage (UMK) is a wage policy that must be implemented by all districts/cities, including Cilegon City. However, violations of wage payments that do not comply with regulations still occur. The Cilegon City Manpower Office and the Labor Inspection Unit (UPTD) play key roles in monitoring and enforcing the policy, with Law No. 6 of 2023 serving as its legal basis. This study aims to analyze the implementation of the UMK policy and its driving and inhibiting factors using Merilee S. Grindle’s theory. It employs a descriptive qualitative method through interviews and observations, with purposive and snowball sampling techniques. The findings indicate that the UMK policy is intended to ensure workers’ decent living standards, wage certainty, and a balance between workers and employers. However, challenges remain, especially among service providers and small to medium enterprises prone to violations. Supporting factors include stakeholder commitment, policy benefits, and effective communication, while inhibiting factors include limited government capacity, tender system issues, budget constraints, dual complaint mechanisms, and weak supervision. Recommendations include strengthening institutional capacity, improving coordination, and enhancing supervision.